Pengaruh Promosi, Kualitas Produk dan Harga Terhadap Minat Beli pada Dealer Honda Daya Motor Tambun - Jihan Ghina Nur Azizah; Andrian Andrian (Indo Publishing, 2026)
The Indonesian motorcycle industry continues to grow along with rising public demand for personal vehicles. Honda dominates the national market with a share exceeding 70%, including through Honda Daya Motor Tambun Dealer in Bekasi; however, this dealer faces fluctuating sales that warrant further study. This study examines the influence of promotion, product quality, and price on consumer purchase intention for Honda motorcycles at Honda Daya Motor Tambun Dealer, both partially and simultaneously. A quantitative approach was employed, involving 100 respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using multiple linear regression with SPSS. The results show that promotion, product quality, and price each have a positive and significant effect on purchase intention, with price as the most dominant factor. Simultaneously, the three variables significantly affect purchase intention and explain 40.8% of its variance. These findings indicate that consumers prioritize price competitiveness, so the dealer should set competitive prices while maintaining product quality and promotional effectiveness to stimulate purchase intention.